The Legal Status of a Breached Indemnity Agreement in the Submission of Surety Bond Claims (Case Study of Decision No. 780/Pdt.G/2022/PN Jkt.Pst): Kedudukan Hukum Perjanjian Ganti Rugi (Indemnity Agreement) yang Wanprestasi dalam Proses Pengajuan Klaim Surety Bond (Studi Kasus Putusan No. 780/Pdt.G/2022/PN Jkt.Pst) - Wijaya, Jonathan; Djajaputra, Gunawan (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Surety bonds function as key legal instruments ensuring performance in Indonesia’s construction and procurement sectors. Specific Background: When a principal defaults and the surety pays the obligee’s claim, the indemnity agreement becomes central to determining the surety’s right of recourse. Knowledge Gap: However, limited scholarly attention has examined the legal force of breached indemnity agreements and the procedural barriers that may obstruct enforcement. Aims: This study analyzes the legal status and binding effect of indemnity agreements when principals fail to reimburse sureties, using District Court Decision No. 780/Pdt.G/2022/PN Jkt.Pst as a case study. Results: Findings show that the indemnity agreement constitutes an independent and binding contract under Article 1338 of the Civil Code, giving the surety an automatic and unconditional right of recourse once a claim is paid. The principal’s non-payment constitutes clear breach, triggering liability for reimbursement, penalties, and legal costs. Nonetheless, the lawsuit was declared inadmissible due to error in persona, preventing substantive examination. Novelty: This study demonstrates that substantive contractual strength alone is insufficient without procedural precision in constructing parties to the lawsuit. Implications: Effective enforcement of surety rights requires harmonizing contractual validity with strict procedural compliance to ensure legal certainty. Highlights: The indemnity agreement holds independent and binding legal force, giving the surety an unconditional right of recourse. Principal’s failure to reimburse constitutes clear breach, triggering liability for reimbursement, penalties, and legal costs. Procedural errors (error in persona) can nullify an otherwise strong substantive claim, preventing judicial examination. Keywords: Indemnity Agreement, Surety Bond, Breach of Contract, Right of Recourse, Error in Persona